Pengaruh Green Accounting, Corporate Social Responsibility, dan Struktur Modal Terhadap Kinerja Keuangan - Kharisma Apriliana Putri; Zaenal Wafa (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to determine the influence of the implementation of green accounting, corporate social responsibility (CSR), and capital structure on the financial performance of coal mining companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The research method used is quantitative with a multiple linear regression approach. The research sample was taken by purposive sampling of 15 companies for 3 years, so that 45 data were obtained which were analyzed using secondary data from financial statements and sustainability reports. The results of the study show that green accounting and Corporate Social Responsibility have a negative and significant effect on financial performance, while capital structure has a positive and significant effect on financial performance. These findings indicate that the company's environmental costs and Corporate Social Responsibility activities have not had a direct positive impact on short-term financial performance, but investments in capital structure management can significantly improve financial performance. This research provides important insights for mining companies to efficiently manage environmental and Corporate Social Responsibility costs and balance capital structures to maintain and improve financial performance while supporting corporate sustainability.